Collaborative Writing Projects: Set Yourself up for Success. Issue 4 (15th July 2021) - Catanzano, Tara; Robbins, Jessica B.; Schwartz, Fides R.; Rajiah, Prabhakar; Wang, Sherry S.; Nandwana, Sadhna; Soloff, Erik V.; Folio, Les R.
Abstract: This article will review critical components for the successful completion of a multi-institution, multiauthor collaborative paper. Best practices for the creation and publication of a collaborative paper will be addressed.